Biomimetic Nanochannels: From Fabrication Principles to Theoretical Insights. Issue 4 (25th February 2022) - Kan, Xiaonan; Wu, Chenyu; Wen, Liping; Jiang, Lei
Abstract: Biological nanochannels which can regulate ionic transport across cell membranes intelligently play a significant role in physiological functions. Inspired by these nanochannels, numerous artificial nanochannels have been developed during recent years. The exploration of smart solid‐state nanochannels can lay a solid foundation, not only for fundamental studies of biological systems but also practical applications in various fields. The basic fabrication principles, functional materials, and diverse applications based on artificial nanochannels are summarized in this review. In addition, theoretical insights into transport mechanisms and structure–function relationships are discussed. Meanwhile, it is believed that improvements will be made via computer‐guided strategy in designing more efficient devices with upgrading accuracy. Finally, some remaining challenges and perspectives for developments in both novel conceptions and technology of this inspiring research field are stated. Abstract : By mimicking biological nanochannels, selective ionic or molecular transport can be realized in artificial smart solid‐state nanochannels. Combinations of different fabrication rules and materials have been explored, which can be applied in various fields, ranging from sensors to energy conversion devices. The underlying mechanisms are studied through simulations, which can provide further guidance for design strategies in turn.